How does radiotherapy affect the adhesion of universal adhesive to enamel and dentin? a qualitative and quantitative analysis? = Efecto de la radioterapia a la adhesión del adhesivo universal al esmalte y dentina? un análisis cualitativo y cuantitativo? - Oglakci, Burcu; Burduroğlu, Defne 1976-; Hikmet Eriş, Ali; Mayadağlı, Alpaslan; Arhun, Neslihan (2022)
This study investigated the shear bond strength (SBS) of a universal adhesive to enamel/dentin; 1) that had undergone radiotherapy (RT) and 2) that were readily restored and had undergone RT. Enamel and dentin surfaces were obtained from 90 intact human molars. They were randomly divided into six groups according to the presence and timing of irradiation (RT0:no radiotherapy/control, RT1:RT before restoration, RT2:RT after restoration groups) and adhesive application modes (etch&rinse/ER, self-etch/SE)(n=15). A universal adhesive and resin composites were applied. The radiotherapy protocol was conducted with 60 Gy. The SBS test was subjected (1mm/min) and failure type analysis was performed. The resin-enamel/dentin interfaces were examined. Data were statistically analyzed. For enamel and dentin, the presence and timing of irradiation did not significantly influence the SBS values (p>0.05). For enamel, significantly higher SBS values were obtained using etch&rinse mode than self-etch mode (p<0.05). The predominant failure was mixed type. Loss of enamel prisms and obliterated irregular dentinal tubules were found for the radiotherapy-treated specimens. Resin tags were clearer in the irradiated enamel treated with ER than SE. Irradiation with different timings did not influence the bond strength to enamel and dentin, negatively. Irrespective of radiotherapy, the etch&rinse mode caused higher bond strength to enamel than self-etch mode.
Este estudio investigó la fuerza de unión al cizallamiento (SBS) de un adhesivo universal al esmalte/dentina en piezas que se habían sometido a radioterapia (RT). Se obtuvieron superficies de esmalte y dentina de 90 molares humanos intactos. Se dividieron aleatoriamente en seis grupos según la presencia y el momento de la irradiación (RT0: sin radioterapia/control, RT1: RT antes de la restauración, RT2: RT después de la restauración considerando los modos de aplicación del adhesivo (n=15). Se aplicó un adhesivo universal y resinas compuestas. El protocolo de radioterapia se realizó con 60 Gy. Se sometió a la prueba adhesiva (1mm/min) y se realizó análisis del tipo de falla. Se examinaron las interfases resina-esmalte/dentina. Los datos fueron analizados estadísticamente. Para el esmalte y la dentina, la presencia y el momento de la irradiación no influyeron significativamente en los valores adhesivos (p>0,05). Para el esmalte, se obtuvieron valores adhesivos significativamente más altos utilizando el modo de grabado y enjuague que el modo de autograbado (p<0,05). La falla predominante fue de tipo mixto. Se encontró pérdida de prismas de esmalte y túbulos dentinarios irregulares obliterados en las muestras tratadas con radioterapia. La irradiación con diferentes tiempos no influyó negativamente en la fuerza de unión al esmalte ni a la dentina. Independientemente de la radioterapia, el modo de grabado ácido y enjuague provocó una mayor fuerza de adhesión al esmalte que el modo de autograbado.
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB